Synthesis, crystal structure and Hirshfeld surface analysis of N-(4-methoxyphenyl)picolinamide - Burieva, Dilnoza; Torambetov, Batirbay; Bobonazarova, Sarvinoz; Abdushukurov, Anvar; Kholikov, Tursinali; Khan, Akram A; Ashurov, Jamshid; Yusufov, Mukhriddin (Acta Crystallographica Section E: Crystallographic Communications, 2024)
The synthesis, <a class="ref_lookup_yellow hideyellow" href="https://dictionary.iucr.org/Crystal_structure" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">crystal structure, and Hirshfeld surface analysis of N-(4-methoxyphenyl)picolinamide (MPPA), C13H12N2O2, are presented. MPPA crystallizes in the monoclinic <a class="ref_lookup_yellow hideyellow" href="https://dictionary.iucr.org/Space_group" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">space group P21/n, with a single molecule in the <a class="ref_lookup_yellow hideyellow" href="https://dictionary.iucr.org/Asymmetric_unit" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">asymmetric unit. Structural analysis reveals that all non-hydrogen atoms are nearly coplanar, and the molecule exhibits two intramolecular hydrogen bonds that stabilize its conformation. Supramolecular features include significant intermolecular interactions, primarily C—H⋯π and various hydrogen bonds, contributing to the overall crystal cohesion, as confirmed by energy framework calculations yielding a total interaction energy of −138.3 kJ mol−1. Hirshfeld surface analysis indicates that H⋯H interactions dominate, followed by C⋯H and O⋯H interactions, highlighting the role of <a class="ref_lookup_orange hideorange" href="https://goldbook.iupac.org/V06597.html" style="text-decoration-line: none; color: rgb(0, 0, 0); font-family: Verdana, Arial, Helvetica, sans-serif;" target="Navigator">van der Waals forces and hydrogen bonding in crystal packing.